Interactions Between Natural Products and Tamoxifen in Breast Cancer: A Comprehensive Literature Review - Yen, Christine; Zhao, Fan; Yu, Zhichao; Zhu, Xiaoshu; Li, Chun Guang (Frontiers in Pharmacology, 2022)
Introduction: Tamoxifen (TAM) is the most commonly used hormone therapeutic drug for the treatment of estrogen receptor positive (ER +) breast cancer. 30%-70% of clinical breast cancer patients use natural products, which my increase the likelihood of drug interactions. Objective: To evaluate the evidence for the interactions between natural products and TAM in breast cancer. Methods: Electronic databases, including PubMed, CINAHL Plus (via EbscoHost), , European PMC, Medline, and Google Scholar were searched for relevant publications. The search terms include complementary and alternative medicine, natural products, plant products, herbs, interactions, tamoxifen, breast cancer and their combinations. Results: Various in vitro and in vivo studies demonstrated that the combined use of natural products with TAM produced synergistic anti-cancer effects, including improved inhibition of tumor cell growth and TAM sensitivity, and reduced side effects or toxicity of TAM. On the other hand, some natural products including Angelicae sinensis, Paeoniae alba, Romania glutinous, Astragals membranaceus and Glycyrrhiza glabra showed estrogen-like activity which may reduce the anti-cancer effect of TAM. Some natural products, including jasmonic acid, silybin, epigallocatechin gallate (EGCG), myricetin, baicalein, curcumin, kaempferol or quercetin were found to increase the bioavailability of TAM and its metabolites in vivo. However, three are limited clinical studies on combination of natural products and TAM. Conclusion: There is evidence for potential interactions of various natural products with TAM in pre-clinical studies, although the relevant clinical evidence is still lacking. Further studies are warranted to evaluate potential interactions of natural products with TAM in clinical settings.